Teknik Vokal pada Kesenian Burdah - Hary Murcahyanto; Yuspianal Imtihan; Mohzana Mohzana; Nurul Hikmah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the vocal techniques used in singing Burdah's verse. This research uses descriptive qualitative method. The object of research is focused on vocal technique problems while the research subject is Jama'ah Burdah Al-Istiqlal, East Lombok. The results showed that the Burdah vocal technique had to use special lyrics or Barzanji. Not all of the vowel articulations are pronounced clearly according to the Arabic language. Burdah is sung at a slow tempo with a speed value of 60-63 (Larghetto). The dynamics at the beginning of the rhyme will sound louder and louder after which the same until the end except at the beginning again because the same rhythm is repeated. Frashering said to Burdah that he always welcomed each other so that the chanting would not break. Uses abdominal and upper resonance breathing as it is very influential on high notes. The conclusions of the study were found regarding the use of special rhymes, not all of the articulations were pronounced clearly, slow tempo, moderate dynamics, getting louder and repetitive, unbroken word decapitation, using abdominal breathing and upper resonance. Keyword: Burdah, Religious Art, Vocal Technique